5G based Blockchain network for authentic and ethical keyword search engine. Issue 5 (2nd July 2021) - M, Poongodi; Malviya, Mohit; Hamdi, Mounir; V, Vijayakumar; Mohammed, Mazin Abed; Rauf, Hafiz Tayyab; Al‐Dhlan, Kawther A.
Abstract: The evolution of 4G telecommunication propagated various resource‐crunched clients to experience rate‐effective resources at ease. However, it extends its underlying centralised architecture, which arouses various challenges correlated with network data availability, network information protection, and operational infrastructure charges. With the recent revolution of telecommunication, 5G networks promised to provide credible schemes like the high quality of service, ultra‐low latency, and much security over the pre‐existing architecture. However, the deployment of end‐to‐end 5G network cutting‐edge systems in the present heterogeneous world limits its core idea of extensive data privacy, native interoperability, risk‐free interference, and radio spectrum sharing. Perhaps, to achieve its true capability, improved versions of blockchain technology could be aligned to strengthen various real‐time complex applications at a flourishing rate. One of the multiplexed real‐time enterprise applications is a keyword search engine where the integrity of user data files and keyword searches are bound to come under cyber hackers. On the one hand, it was found that when a 5G‐based blockchain emulated network gets deployed with intact encryption techniques, the entire system facilitates to give reliable, efficient, and risk‐free keyword search over variegated 5G network data and its complex computational calculations. Consequently, the use of blockchain‐based decentralised cloud orchestration scheme at various levels enabled the architecture to remain incorruptible and protects all the confidential files and keywords in a fully controlled file access environment. The results of the simulation kernel shows that proposed architecture which, when combined with blockchain‐based decentralised cloud orchestration network system, justify all the essential characteristics and effectuates the optimal use of 5G network sharing by each network entity.